Agrosilvopastoril v 19.1: Modeling cattle production and environment contribution of silvopastoral systems in the peruvian tropics - Gómez C. (2020)
Simulation tools can be helpful for supporting implementation of livestock production systems and exploring ways of improvements. The aim of this paper is to present a support tool for implementation and evaluation of silvopastoral systems in the Peruvian Amazon Region. This approach is based on the design of a decision support model called Agrosilvopastoril v 19.1. It calculates livestock production using integrated information on climate, soil, crops, forestry, pastures and cattle herds collected from secondary sources and on-field work conducted at the Peruvian Northern Amazon Region. The model was tested to estimate carbon sequestration and enteric methane emissions in 10 has of silvopastures with different proportions of forest and pasture, showing an increase in carbon sequestration with a small reduction in the number of animals and similar methane emissions.